REFLECTION, IMPLEMENTATION, AND CONSEQUENCES OF ARTICLE 33 OF THE 1945 CONSTITUTION (AFTER AMENDMENT) TOWARDS THE ECONOMY OF INDONESIA AND ISLAMIC ECONOMIC CONNECTION - Syafwendi Syafril (Airlangga International Journal of Islamic Economics and Finance, 2020)
Indonesia is one of the world's largest country is strategically located betweentwo continents and two oceans. Strategic location endows Indonesia withabundant natural resources from the sea, air, and land area. Besides havingabundant natural resources, Indonesia has rich in culture, language, andcustoms, as well as demographic conditions. With the potential and assetsowned by Indonesia, this country has the opportunity to be a progressive andgrowing rapidly country.The committee was formed by the unification ofperception through legislation by the central government to support economicprosperity for the sake of welfare for all Indonesian people. So with thiscommitment is raised regulation of 33 UUD 1945, as one form betweengovernment and society to advance Indonesia's economy, so that will beexpected to improve the sustainable development, utilization of naturalresources to support the benefit of many people's lives, and that isn’t equallyimportant is the creation of social welfare for Indonesian society. But these loftyambitionsaren’t going according to what was expected earlier, the attitude ofindividualism that is more about profitability than the social welfare is moreprominent in the implementation of Article 33 UUD 1945, especially after thepoint of the article was amended.